Evaluation of a Simpler Technique for In-Vivo Labelling of Red Blood Cells with 99mTc - Rehani, M. M.; Sapru, R. P.; Chopra, V. K.; Sharma, R. R.; Wahi, P. L. (Nuklearmedizin - NuclearMedicine, 1980)
The efficiency of labelling red blood cells with intravenously administered 99mTc04, by prior oral administration of stannous chloride dihydrate, has been evaluated. Optimum labelling occured 1 hr after the oral dose of 200 mg of SnCl2 · 2 H20 and 20 min after the intravenous injection of 99mTc04. The mechanism of labelling has been shown to be diffusion of 99mTc through the cell membrane followed by binding to haemoglobin in the presence of reducing agent. The in-vivo labelling technique has been found to be useful for the diagnosis of an abdominal mass and for static perfusion studies.